Resolving the taxonomic puzzle of Boana cinerascens (Spix, 1824), with resurrection of Hyla granosa gracilis Melin, 1941 (Anura: Hylidae) - Sturaro, Marcelo José; Costa, João Carlos Lopes; Maciel, Adriano O.; Lima-Filho, Geraldo R.; Rojas-Runjaic, Fernando J. M.; Mejia, Daniela Pareja; Ron, Santiago R.; Peloso, Pedro L. V. (Zootaxa, 2020)
Expeditions to unexplored or little explored places are important for discovering new species and also for collecting new samples (including specimens and tissues for DNA sequencing ) that may help resolve a plethora of taxonomic problems. In the 19th century, several naturalists explored a number of localities in Amazonia, describing species for which type material was deposited, mostly, in European museums of natural history. Some of these types were lost or destroyed in World War II and recent expeditions have focused on sampling new material from the type localities. material from Boana cinerascens, which allowed us to infer phylogenetic relationships of the Boana punctata group (i.e., green Boana), based on DNA sequence data, and to revaluate the status of B. cinerascens and its synonyms. We designate, redescribe and illustrate a neotype for B. cinerascens, which was described by Spix in 1824, from the Municipality of Tefé, State of Amazonas, Brazil. We revalidate, redescribe, and illustrate Hyla granosa gracilis Melin, 1941(= Boana gracilis). Corroborating previous studies, the green Boana were not recovered as a monophyletic group. Boana cinerascens is sister of B. gracilis plus a clade containing B. atlantica + B. punctata (both species not recovered as monophyletic).